The Role of Audit Committee to Decrease Audit Report Lag - Deny Maulana (UNIVED Press, 2024)
This study aims to investigate the role of the audit committee as a moderator in reducing audit report lag, with independent variables being audit complexity, board size, and board meetings' impact on audit report lag. The sample comprises 96 infrastructure sector companies listed on the Indonesia Stock Exchange for the years 2022-2023.The findings reveal that the audit complexity (ACX) variable does not significantly positively influence audit report lag, while the board size (BOS) variable does not significantly negatively affect audit report lag. However, the board meetings (BOM) variable shows a significant negative impact on audit report lag. Furthermore, the audit committee (ACOM) strengthens the influence of audit complexity (ACX) on audit report lag and also enhances the influence of board size (BOS) on audit report lag. However, the audit committee (ACOM) does not strengthen the influence of board meetings (BOM) on audit report lag. In summary, this study sheds light on the moderating role of the audit committee in reducing audit report lag, highlighting the varying effects of audit complexity, board size, and board meetings on audit report timeliness within the IDX infrastructure sector.